1998
DOI: 10.1073/pnas.95.26.15327
|View full text |Cite
|
Sign up to set email alerts
|

Cytologically normal cells from neoplastic cervical samples display extensive structural abnormalities on IR spectroscopy: Implications for tumor biology

Abstract: Fourier-transform IR (FT-IR) spectra of pelleted exfoliated cervical cells from patients with cervical cancer or dysplasia differ from those from normal women. To study the origin of these spectral changes, we obtained the FT-IR spectra of individual cervical cells from normal, dysplastic, and malignant cervical samples. Ninety five percent of normal superficial and intermediate cells displayed two distinct spectral patterns designated A and B, and 5% displayed an intermediate pattern, suggesting extensive str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
116
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(126 citation statements)
references
References 10 publications
9
116
1
Order By: Relevance
“…Several comprehensive books and articles outline the field [22][23][24][25]. One area that has received considerable attention was the application of the FTIR technique to the diagnosis of cervical neoplasia [26][27][28][29][30][31][32][33][34][35]. Early studies reported spectral differences between exfoliated cells from patients diagnosed normal and dysplastic by cytological [26,27] and histological methods [28,30].…”
Section: The Infrared Alternativementioning
confidence: 99%
“…Several comprehensive books and articles outline the field [22][23][24][25]. One area that has received considerable attention was the application of the FTIR technique to the diagnosis of cervical neoplasia [26][27][28][29][30][31][32][33][34][35]. Early studies reported spectral differences between exfoliated cells from patients diagnosed normal and dysplastic by cytological [26,27] and histological methods [28,30].…”
Section: The Infrared Alternativementioning
confidence: 99%
“…In spite of these obstacles, work by Cohnford and Rigas [81] relatively early pointed out one of the most relevant aspects of SCP, namely that most cells from an abnormal cervical sample exhibit spectra that are more closely related to the spectral patterns of diagnostic abnormal cells than to those of normal cells. This is true for cells still with normal morphology and therefore, offers the prospects of developing a test with much higher sensitivity than classical cytopathology, since more cells present abnormal properties.…”
Section: Introductionmentioning
confidence: 99%
“…IR spectroscopy became a powerful tool for cell line identification, biodiagnostics and prognostics. 9,10 In vitro, closely related cancer cells could be distinguished. For instance, the FTIR spectra of various human glioma cell lines were shown to be strongly correlated with their aggressiveness in vivo.…”
Section: Introductionmentioning
confidence: 99%